Marketing strategy of Tangerang culineria as one of the culinary tourism objectives in Tangerang City / Cahyani Kurniastuti - Kurniastuti, Cahyani (UiTM Cawangan Johor, 2019)
Laksa is a traditional food popular in the city of Tangerang and is one of the culinary attractions in the city of Tangerang. Along with the development of the city of Tangerang which is rife with the establishment of the mall, especially the Tang City Mall, which is located quite close to the Laksa district, presents challenges and threats to the existence of a fast food culinary business. With this research, it is hoped that it can produce a marketing strategy in developing the culinarian Laksa of Tangerang so that it can increase the public interest of travel culinary both within and outside the city of Tangerang. It is hoped to increase income for laksa sellers and provide employment opportunities for the people of Tangerang City. This study focused on qualitative research with data collection techniques involving direct observations, in-depth interviews, distributing questionnaires. The data analysis method applied in this study using Matrix analysis of EFAS (External Factor Analysis Summary), matrix of IFAS (Internal Factor Analysis Summary), SWOT Matrix (Strength, Weakness, Opportunity, Threats), QSPM (Quantitative Strategic Planning Matrix).